2019
DOI: 10.3389/fpsyg.2019.02028
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Reorientation and Inhibition Adjustment in a Verbal Stroop Task: A Lifespan Approach to Interference and Sequential Congruency Effect

Abstract: Several parameters influence the interference effect elicited in a Stroop task, especially contextual information. Contextual effects in the Stroop paradigms are known as the Gratton or Sequential congruency effect (SCE). This research aims at isolating two processes contributing to the SCE in a Stroop paradigm, namely attentional reorientation from the color to the word and vice-versa, as well as inhibition (engagement/disengagement from one trial to the next one). To this end, in Study 1 subprocesses of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 99 publications
(182 reference statements)
1
9
0
Order By: Relevance
“…Another explanation might be related to the structure of the task. Since initially this task was designed to investigate the conflict adaptation effect [40], up to three repetitions of the same condition were allowed. Subjects might have benefit from this feature to anticipate the presence of a conflict in the next item.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another explanation might be related to the structure of the task. Since initially this task was designed to investigate the conflict adaptation effect [40], up to three repetitions of the same condition were allowed. Subjects might have benefit from this feature to anticipate the presence of a conflict in the next item.…”
Section: Discussionmentioning
confidence: 99%
“…The participants were part of a larger group from which only the behavioral data has been analyzed in previous study [40].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that the task of focusing on the "right" answer in a conflictual situation is related to a part of the brain called anterior cingulate, a region located in the frontal lobe. It is involved in many higher cortical processes including attention and executive functioning (Banich, 2019;Ménétré & Laganaro, 2019).…”
Section: Introductionmentioning
confidence: 99%